Between then and fold: feelings of patients on dialysis - Amanda Emilia Seabra de Melo, Jadh Wilker Xavier, Flávia Itaguacy da Silva Brito, Vinicius Lino de Souza Neto, Ana Elza Oliveira de Mendonça (Revista de Enfermagem da UFPI)
DOI: https://doi.org/10.26694/reufpi.v3i4.2826